Tinjauan Reformasi Pendidikan Islam di Islamic Centre Bin Baz : Studi Kasus Pengaruh Pendidikan Islam - Muhamad Nuur Rasyid; Ai Fatimah Nur Fuad; Muhammad Abdullah Darraz (Journal on Education, 2024)
This research aims to analyze the impact of the Islamic education reform implemented at the Bin Baz Islamic Centre. The main focus of the research is to identify the development of students in cognitive, affective, and psychomotor aspects. In order to achieve these objectives, the research proposes the need for reform in the curriculum and teaching methods applied at the institution. A qualitative approach with a descriptive method is chosen as the methodological framework to provide an in-depth understanding of the influence of educational reform. Data analysis follows the Miles and Huberman model. Data collection is carried out through observations, interviews, and document analysis. The qualitative approach, with a focus on the role of informants as data sources, allows the research to investigate complex aspects within the context of Islamic education reform. The results of this research emphasize the urgency of education in shaping a holistic understanding, not only within the family environment but also involving the significant role of schools and colleges. In terms of the curriculum, it has been implemented effectively, accompanied by careful teaching strategies to achieve optimal teaching effectiveness. However, the research also identifies some challenges, particularly in the context of learning the Indonesian language, where some students are not fully engaged, exhibiting behaviors of sleeping or playing alone. Therefore, the author compiles this scholarly work to be viewed as an effort to enhance student engagement and, consequently, the quality of education at the institution.